1970
DOI: 10.1136/bmj.1.5688.110
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphataemia and hypokalaemia.

Abstract: Most of Dr. Birdwood's missionary zeal is harmless, and some of it is a useful reminder of our age-old obligations to the sick. But I must protest at his attack on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…On the other hand, the possibility that hypokalaemia may itself be a cause of hypophosphataemia is suggested by the findings of Anderson et al (1969), who reported low serum phosphorus levels, associated with increased urinary phosphorus excretion, in 13 patients with hypokalaemia due to a variety of causes, in 10 of whom the levels rose on correction of the potassium level with oral Slow-K. These results were confirmed by Condon and Nassim (1970), who noted a persistent fall in serum phosphorus of more than 1 mg/100 ml in seven patients taking bendrofluazide for hypercalciuria. They thought that an intracellular potassium deficiency over a long time might cause renal tubular damage, resulting in a renal tubular phosphate leak.…”
Section: Hypophosphataemia: Possible Causesmentioning
confidence: 84%
See 2 more Smart Citations
“…On the other hand, the possibility that hypokalaemia may itself be a cause of hypophosphataemia is suggested by the findings of Anderson et al (1969), who reported low serum phosphorus levels, associated with increased urinary phosphorus excretion, in 13 patients with hypokalaemia due to a variety of causes, in 10 of whom the levels rose on correction of the potassium level with oral Slow-K. These results were confirmed by Condon and Nassim (1970), who noted a persistent fall in serum phosphorus of more than 1 mg/100 ml in seven patients taking bendrofluazide for hypercalciuria. They thought that an intracellular potassium deficiency over a long time might cause renal tubular damage, resulting in a renal tubular phosphate leak.…”
Section: Hypophosphataemia: Possible Causesmentioning
confidence: 84%
“…However, in the case reported by Vianna (1971) of a patient who developed hypophosphataemia secondary to hypokalaemia and alkalosis after long-standing ingestion of liquorice and hydrochlorothiazide, and whose phosphorus level rose to normal after correction of the potassium deficit, no other possible causative factors were present. Vianna discarded the possibility that the thiazides, the liquorice, or the alkalosis caused the hypophosphataemia and postulated a similar mechanism to that suggested by Condon and Nassim (1970)-namely, a renal phosphate leak. Thus hypokalaemia seems to be established as a cause of hypophosphataemia and may be the factor operating in severe liver disease or in the administration of thiazides.…”
Section: Hypophosphataemia: Possible Causesmentioning
confidence: 98%
See 1 more Smart Citation
“…Sterile 20 kinase TRPC Transient receptor potential canonical channel TRPV Transient receptor potential vanilloid channel homeostasis was indirect and via renal Ca 2+ homeostasis. [35][36][37] This was further supported by research showing that the renal transient receptor potential vanilloid (TRPV) ion channels involved in Ca 2+ transport are WNK regulated. In fact, TRPV5 expression is localized to the apical membrane of the DCT, the nephron segment involved in active Ca 2+ reabsorption, which is positively regulated by both WNK4 and WNK3.…”
Section: Fhhtmentioning
confidence: 90%
“…Data from as far back as the late 1960s show a link between thiazides and increased BMD, hypocalciuria and hypophosphatemia, suggesting the role of WNKs in bone homeostasis was indirect and via renal Ca 2+ homeostasis . This was further supported by research showing that the renal transient receptor potential vanilloid (TRPV) ion channels involved in Ca 2+ transport are WNK regulated.…”
Section: Extrarenal Physiological Rolesmentioning
confidence: 94%